Does Policing Help or Hurt?: Examining the Longitudinal Relationship Between Police Involvement and Delinquency in Norway - Andersen, Synøve Nygaard (The British journal of criminology, 2024)
The population heterogeneity argument links criminality to time-stable individual traits and suggests that criminal justice system involvements exert no independent influence on criminal behaviour. This study directly tests this postulation by estimating the relationship between police involvement and subsequent delinquency in an individual fixed effects design. The analysis relies on five waves of longitudinal data on self-reported delinquency and administrative data on police contacts. Results show that time-stable individual traits matter, but that the frequency of police contacts is positively associated with offending also after such characteristics have been accounted for. The results are thus in line with the state dependence argument and provide tentative support for labelling theory’s postulation that criminal justice involvement increases rather than decreases criminal behaviour.